1988
DOI: 10.1128/aem.54.6.1436-1439.1988
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Assay for Measuring the Number of Bacteria Adhering to the Hydrocarbon Phase in the BATH Test

Abstract: A thorough validation of the bacterial adherence to hydrocarbons (BATH) test was performed by means of a bioluminescence assay. Ten different gram-negative strains were subjected to the BATH test. For the calculation of the adhesion index, several factors had to be taken into account: ATP leakage, the action of ATP-hydrolyzing enzymes, the change in the extraction efficiency of Nucleotide-Releasing Reagent for Microbial Cells (NRB; Lumac bv) after vortexing and the difference in light production after the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Although variable results were found depending on the hydrocarbon, buffer and strain employed, we consider, in agreement with Vanhaecke and Pijck [21], more appropriate the use of hexadecane and PUM buffer, since a higher correlation with the other methods was detected.…”
Section: Discussionsupporting
confidence: 84%
“…Although variable results were found depending on the hydrocarbon, buffer and strain employed, we consider, in agreement with Vanhaecke and Pijck [21], more appropriate the use of hexadecane and PUM buffer, since a higher correlation with the other methods was detected.…”
Section: Discussionsupporting
confidence: 84%
“…The bacterial adherence to hydrocarbons (BATH) test was performed as described by and Weiss et al (44), using hexadecane and octane as organic test fluids. Xylene was excluded from the test because it was found to produce unreliable hydrophobicity results (38).…”
Section: Measurement Of Bacterial Cell Hydrophobicity (I) Bathmentioning
confidence: 99%
“…(i) Instrumentation and reagents. Light production was measured by using Lumit-PM (luciferin-luciferase reagent) in a Lumac Biocounter M2010 (Lumac bv, Landgraaf, The Netherlands) (20,27,38). Nucleotide-releasing reagent for microbial cells (NRB) (Lumac) was used as the bacterial ATP-releasing agent.…”
Section: Measurement Of Bacterial Cell Hydrophobicity (I) Bathmentioning
confidence: 99%
“…Many investigators have modified the original MATH test and have found that seemingly small variations in experimental conditions, such as the diameter of the test tubes, the pH of the suspension medium, and the volume of hydrocarbon used, can significantly alter the results (4,17,30). Aliphatic hydrocarbons are used in most cases, since aromatic hydrocarbons cause lysis of some bacterial species (55).…”
mentioning
confidence: 99%